Genetic population structure and connectivity of Azorean limpets - Faria, João (2014)
There is growing consensus that anthropogenic activities significantly rarefy the structure and functioning of marine ecosystems. Oceanic islands such as the Azores (NE Atlantic) constitute unique habitats with fragile communities, which are highly susceptible to degradation and ecosystem disruption. . Patellid limpets have traditionally been collected as a food resource and in 1988 the limpet fishery in São Miguel Island collapsed, and after a one-year ban throughout the archipelago, the stocks were allowed to recover, avoiding catastrophic overexploitation effects. In 1993, legislation was passed to protect this resource, i.e. limpet no-take areas were created, seasonal harvesting restrictions were applied and minimum legal catch sizes were established. However, a recent survey has shown that limpet populations still show clear signs of overexploitation and some populations are virtually extinct in some islands. Here we have developed new multiplexed and described microsatellite markers for the species Patella aspera and P. candei and have examined their genetic diversity, gene flow and population connectivity in the Azores Archipelago. Overall, such information is a fundamental asset to inform conservation strategies and to promote the sustainable exploitation of macaronesian limpets.